Association between KCNQ1 gene polymorphisms and gestational diabetes mellitus susceptibility in a Chinese population - Yanying Wu; Yanying Wu; Yanying Wu; Yuxuan Zhang; Yuxuan Zhang; Yuxuan Zhang; Xin Liu; Xin Liu; Xin Liu; Jia Liu; Jia Liu; Jia Liu; et al. (Frontiers in Endocrinology)
IntroductionThe potassium voltage-gated channel subfamily Q member 1 (KCNQ1) gene is recognized as a type 2 diabetes mellitus (T2DM) susceptibility gene. However, there is limited data regarding the association between KCNQ1 gene polymorphisms and gestational diabetes mellitus (GDM) susceptibility in China. To explore the association between KCNQ1 gene polymorphisms and GDM susceptibility in a Chinese population.MethodsWe conducted a case-control study including 500 pregnant women with GDM and 502 pregnant women with normal glucose tolerance (as controls). Blood samples and clinical data were collected. KCNQ1 gene rs2237897, rs163184, rs151290, and rs2237892 were genotyped by SNPscan™ genotyping assay. Using SPSS V.26.0, statistical analysis was performed to explore the association of KCNQ1 gene polymorphisms with GDM and genotypes with blood glucose levels. Meta-analysis was further validated in different populations.ResultsAfter being adjusted for confounding factors (age, parity, pre-pregnancy BMI (pre-BMI) and blood pressure) and Bonferroni correction, rs2237897 showed an association with decreased GDM risk in codominant heterozygous (CT vs. CC: OR = 0.537; 95% CI: 0.354-0.816; P = 0.004) and overdominant models (CT vs. CC+TT: OR = 0.533; 95% CI: 0.355-0.801; P = 0.002) in pregnant women aged < 30 years. However, rs2237892, rs151290, and rs163184 did not found associations with GDM after Bonferroni correction. Meta-analysis showed that rs2237892 was associated with decreased GDM risk in different races in dominant (TC+TT vs. CC: OR = 0.830; 95% CI: 0.699-0.985; P = 0.033), recessive (TT vs. CT+CC: OR = 0.733; 95% CI: 0.612-0.877; P = 0.001), codominant homozygous (TT vs. CC: OR = 0.679; 95% CI: 0.562-0.820; P < 0.001), codominant heterozygous (TC vs. CC: OR = 0.843; 95% CI: 0.753-0.945; P = 0.003) and allele models (T vs. C: OR = 0.852; 95% CI: 0.740-0.982; P = 0.027).ConclusionKCNQ1 rs2237897 is associated with decreased GDM risk in a Chinese population. Although rs2237892 did not found association with GDM risk in our subjects, meta-analysis confirmed that rs2237892 is associated with reduced GDM risk across different populations. Further studies are needed to confirm these findings and elucidate the mechanisms.